Development of the sex industry and the spread of prostitution in advanced European civilization - Goldsmith, Jemima; Brown, Sarah; Robert, Alice (PT. Riset Press International, 2023)
This paper presents a comprehensive sex industry typology based on primary data collected between 2020 and 2022. Contemporary sex industry typologies in Europe tend to be sector-specific or have been developed from specific disciplinary perspectives or themes (e.g. sexual health programs, income). Set within the typological context of the international sex industry, this paper seeks to address this gap. Data was obtained from online surveys, questionnaires and consultations with stakeholders including individuals currently or previously involved in selling sex, service providers/NGOs, police, local government representatives and others. The data is complemented by insights from a systematic literature search. This work aims to assist program and policy planning in the Europe context. Our method can help develop typologies in other contexts.